AtMOB1 Genes Regulate Jasmonate Accumulation and Plant Development. Issue 3 (20th December 2019) - Guo, Zhiai; Yue, Xiaozhen; Cui, Xiaona; Song, Lizhen; Cheng, Youfa
Abstract : A core component of the Hippo pathway plays important roles in regulating jasmonate accumulation and plant development in Arabidopsis. Abstract: The MOB1 proteins are highly conserved in yeasts, animals, and plants. Previously, we showed that the Arabidopsis ( Arabidopsis thaliana ) MOB1A gene ( AtMOB1A/NCP1 ) plays critical roles in auxin-mediated plant development. Here, we report that AtMOB1A and AtMOB1B redundantly and negatively regulate jasmonate (JA) accumulation and function in Arabidopsis development. The two MOB1 genes exhibited similar expression patterns, and the MOB1 proteins displayed similar subcellular localizations and physically interacted in vivo. Furthermore, the atmob1a atmob1b ( mob1a/1b ) double mutant displayed severe developmental defects, which were much stronger than those of either single mutant. Interestingly, many JA-related genes were up-regulated in mob1a/1b, suggesting that AtMOB1A and AtMOB1B negatively regulate the JA pathways. mob1a/1b plants accumulated more JA and were hypersensitive to exogenous JA treatments. Disruption of MYC2, a key gene in JA signaling, in the mob1a/1b background partially alleviated the root defects and JA hypersensitivity observed in mob1a/1b. Moreover, the expression levels of the MYC2 -repressed genes PLT1 and PLT2 were significantly decreased in the mob1a/1b double mutant. Our results showed that MOB1A/1B genetically interact with SIK1 and antagonistically modulate JA-related gene expression. Taken together, our findings indicate that AtMOB1A and AtMOB1B play important roles in regulating JA accumulation and Arabidopsis development.